A interatividade na aprendizagem: uma perspectiva cognitiva utilizando conteúdo multimídia - Pedra, Agnaldo (2014)
The migration of educational materials to hand-held devices such as tablet computers affords the possibility of offering high levels of interactivity in presenting animations so, research is needed to assess the pedagogic value of incorporating sophisticated interactivity features into lessons on hand-held devices. Engineering students (in Experiment 1) and non-engineering college students (in Experiment 2) spent 5 minutes studying an animation showing a 6-step maintenance procedure for a mechanical device called a Power Take-Off presented on an tablet computer The animation involved low levels of interactivity (i.e., pause and continue buttons on the touch screen), high levels of interactivity (i.e., rotation through dragging movements and zoom through pinching movements as well as pause and continue buttons), or no interactivity (in Experiment 2 only). Overall, across both experiments, students who received high interactivity reported higher interest but did not show better learning as compared to the low or no interactivity group. However, in Experiment 2, students who rated themselves as verbal learners produced higher interest ratings and higher learning scores for high interactivity rather than low or no interactivity, but this pattern was not found for visual learners. Also, in Experiment 2 verbal learners and low self-regulated learners who showed higher level of interest produced higher learning scores than visual learners and high self-regulated learners who showed lower level of interest, respectively.